En torno al derecho moral del autor a la integridad de su obra: reflexiones a propósito del daño efectuado a los murales en el Centro de Lima - Solórzano Solórzano, Raúl (2015)
Based on the recent damage done to the murals in the Centre of Lima, this article analyzes the conflict that can occur between the moral right of authors to the integrity of their work and the property rights of the holders of the support containing the intellectual creation. Criteria are provided to analyze conflicts in which murals are involved. Finally, the infringement of moral right of integrity is discussed.